An Assay to Evaluate the Function of Liposomal Platelet Substitutes Delivered to Platelet Aggregates - Tan, Suyun Janet; Nakahara, Keiko; Sou, Keitaro; Takeoka, Shinji (Frontiers in Bioengineering and Biotechnology, 2019)
Aggregation of liposomal platelet substitutes with activated platelets is the primary endpoint to estimate hemostatic potential. Although light transmission aggregometry is a ‘gold standard’ in assessing platelet aggregation in vitro, this method is less specific and sensitive when tested using liposomal platelet substitutes. In the current study, a new method is developed to evaluate the function of platelet substitutes. By labeling liposomes with a fluorescent dye, DiD, we evaluated their ability to target platelet aggregates using a fluorescence microscope. By incorporating an image-based 96 microtiter microplate, this method was optimized by varying the final lipid concentrations and washing times and validated using unmodified liposomes (e.g. L550 with 0 mol% of carboxylic headgroup lipid; L551 with 9 mol% of carboxylic headgroup lipid) and modified liposomes (e.g. H12-L551 with 9 mol% of carboxylic headgroup lipid and 0.3 mol% of dodecapeptide). Our results showed that 200 µM of H12-L551 liposomes and four washes represent optimal conditions for quantitative fluorescence imaging. This method allowed users to qualitatively observe the fluorescently labeled liposomes involved in platelet aggregates. The imaging analysis tool was sufficiently sensitive to quantitatively determine the significantly enhanced delivery of the modified liposomes to platelet aggregates. This enhancement was achieved using dodecapeptide, which specifically binds to activated platelets. This robust and high-throughput method enables the evaluation of liposome function and should facilitate the development of platelet substitutes with a greater ability to target platelet aggregates.